Devir-revolucionário nos escritos de Caio Fernando Abreu e de Reinaldo Arenas: traçados de um encontro (por vir) - Forster, Gabrielle da Silva (2015)
A dialogic reading between Caio Fernando Abreu and Reinaldo Arenas based on the vitalist and enhanced dimension of their texts is presented here, aiming at articulating a state of uneasiness with the resistant nature that the sight of new existential and relational possibilities opens inside and outside the fictional space. To do so, transgressions as regard the content and form in Arenas and Abreu s fiction were sought - mainly by following the connections existing among the flexibility of Foucault s fold , the new division of the sensible engendered by the political dimension of art in accordance with Ranciere s conception, and the nomad impulse originated by the notion of war machine conceived by Deleuze and Guatarri. Along the trajectory, the revolutionary concept of becoming ; forged through and by the fictional corpus, overcame the dilemma among antagonistic positions presented by the inherent critical view of the selected works in relation to their context of production. By so doing, it was possible to bring to light a transforming way of feeling: one that may alter the existing forms of life and, ultimately, reinvent them. Through different aesthetic devices, the works of fiction studied deviate obstructing centers to allow a becoming to be forseen: unfinished and inoperative, yet, an embryo for a rare community to be thought of, and its alterity restored from its intrinsic expropriation.